1997
DOI: 10.3109/02844319709085481
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Sclerotherapy of Venous Malformations of the Head and Neck Using Sodium Tetradecyl Sulphate (Sotradecol)

Abstract: Thirty-eight patients with venous malformations of the face, neck, and tongue underwent percutaneous sclerotherapy with direct puncture and instillation of sodium tetradecyl sulphate (Sotradecol) (33-67% solution, mixed with contrast material) into the lesions. Each patient underwent from one to seven treatment sessions (mean 2.2), followed by reconstructive surgery in three cases. Of the 34 patients who responded to the follow-up questionnaire, the late results were excellent or good in 23 patients (68%), mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 16 publications
1
88
0
4
Order By: Relevance
“…In this series, no serious complications occurred such facial nerve palsy [8] and blindness [7] which have been reported by others. Post injection inflammatory reactions and pain were recorded in all patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this series, no serious complications occurred such facial nerve palsy [8] and blindness [7] which have been reported by others. Post injection inflammatory reactions and pain were recorded in all patients.…”
Section: Discussionsupporting
confidence: 76%
“…Although the serendipitous discovery of the therapeutic efficacy of propranolol in the management of infantile hemangiomas has revolutionized the care and outcomes of these lesions [5,6], there is no standard treatment protocol for the management of VM. Treatment options of low flow VM include simple observation, minimally invasive interventions such as sclerotherapy or embolization [7,8], laser ablation [9], cryotherapy [10], or more aggressive surgical resection. Management of these lesions varies according to the patient's age, size of the lesion, location, type of the lesion, as well as surgeon experience.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have been published on the safe and effective use of ethanol for the treatment of venous malformations [15,16]. Ethanol is inexpensive and easy to administer.…”
Section: Discussionmentioning
confidence: 99%
“…Although pure ethanol is a very effective sclerosant used to treat VM, the potential for nerve injury in ethanol sclerotherapy can be a significant problem [6,7]. We discussed the risks of ethanol sclerotherapy for pharyngeal VM and concluded that this was not the preferred method for initial intervention in our patient.…”
Section: Discussionmentioning
confidence: 98%